Tinjauan Teoritis Laporan Keuangan Badan Usaha Milik Desa (BUMDES) Berbasis Syariah - Prayogo P. Harto; Ria Riwandari (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2018)
This research aims to determine the form of financial statements Sharia BUMDes. This research using literature review. The accounting standards that form the basis in preparing the financial statements sharia BUMDes are PSAK ETAP, PSAKS Syariah and Permendes No. 4 of 2015 which regulates the establishment, maintenance, management, and dissolution BUMDes. The results of the research explained that the financial statements of sharia BUMDes is different with other businesses, because: 1) BUMDes has dual functions, commercial and social institutions, therefore BUMDes has two types of financial reports, social financial reports and commercial financial reports; 2) The allocation of PAD (Village Income) taken from the profit BUMDes; 3) The additional capital injection of funds ADD (Village Fund Allocation) every year; 4) The revenue reconciliation report and profit sharing which presents the amount of profit sharing BUMDes party and owner of the funds